A backward cycling programme for people with Parkinson's disease: a feasibility and preliminary results study - Suzanne K. O'Neal; Stephanie A. Miller; Megan S. Eikenberry; Elizabeth S. Moore (Medical Journals Sweden, 2024)
Objective: To assess the feasibility of backward cycling for people with Parkinson's disease. Secondary objectives were to assess changes in gait and balance following a 6-week program. Design: A single-group prospective pre-test, post-test study with 1-month follow-up. Subjects/Patients: Twenty-six people with Parkinson's disease (mean age: 69 (7.74) years, gender: 83% males, time since diagnosis: 6 (4.44) years). Methods: Participants pedaled backward on a stationary bicycle for 30 minutes at moderate intensity twice a week for 6 weeks. Feasibility was assessed by acceptability, suitability, and burden. Data collected at pre- and post-intervention with 1-month follow-up included backward stepping response variables, forward/backward gait variables, Mini-Balance Evaluation Systems Test (MBT), and 6 Minute Walk Test. Results: There was a high retention rate (95.8%) and adherence rate (100%) with one adverse event and minimal burden. Significant improvements were seen in step count and excursion distance during backward stepping responses, forward and backward gait velocity, forward step length, and the Mini-BESTest. Conclusion: Backward cycling was a feasible intervention for people with Parkinson's disease, demonstrating low burden with high retention and adherence rates, and it is a safe exercise with the potential for benefits in gait and balance variables.